Phylogeny and systematics of Diptera: Two decades of progress and prospects* - Yeates, David K.; Wiegmann, Brian M.; Courtney, Greg W.; Meier, Rudolf; Lambkin, Christine; Pape, Thomas (Zootaxa, 2007)
The Diptera, or true flies (mosquitoes, gnats, and house flies) comprise 12-15% of animal species, and are the most ecologically diverse order of insects, spanning ecological roles from detritivory to vertebrate blood feeding and leaf mining. The earliest known fossil Diptera are from the early Triassic 240 mya, and the order probably arose in the late Permian. The earliest brachyceran fossils are found in the late Triassic and earliest Jurassic, but the diversification of the extremely diverse Calyptrata (ca. 30% of described species) began in the late Creataceous. The monophyly of the order is supported by numerous morphological and biological characters and molecular data sets. The major lineages within the order are well established, and we summarize major recent phylogenetic analyses in a supertree for the Diptera. Most studies concur that the traditional subordinal group Nematocera is paraphyletic, but relationships between the major lineages of these flies are not recovered consistently. There is particular instability around the placement of the tipulids and their relatives and the families of the Psychodomorpha as traditionally defined. The other major suborder, Brachycera, is clearly monophyletic, and the relationships between major brachyceran lineages have become clearer in recent decades. The Eremoneura, Cyclorrhapha, Schizophora and Calyptrata are monophyletic, however the “Orthorrhapha” and “Aschiza” are paraphyletic, and it is likely that the “Acalyptrata” are also. Ongoing phylogenetic analyses that span the diversity of the order shall establish a robust phylogeny of the group with increased quantitative rigor. This will enable a more precise understanding of the evolution of the morphology, biogeography, biology, and physiology of flies.